PERSPEKTIF MURTAD DALAM PERKAWINAN MENURUT HUKUM POSITIF ISLAM DAN FIKIH 4 IMAM MAZHAB - Efita Nurhidayati; Miftakhul Huda (Jurnal Hukum Saraswati, 2025)
Apostasy before marriage only has an impact on the perpetrator, while apostasy in marriage has an impact on the family. Article 116 letter h of the Compilation of Islamic Law regarding apostasy in marriage is weak, so further discussion is needed. This research uses normative juridical methods with a statutory and conceptual approach, as well as primary, secondary, and tertiary data sources. The results of the study show a difference in perspective between Islamic positive law, namely Article 116 letter h of the Compilation of Islamic Law and Islamic jurisprudence related to apostasy in marriage, especially in terms of tolerance given. In addition, there is a conflict between similar articles and with conflicts with higher provisions